MEASURING DATA ACQUISITION HARDWARE FOR ELECTRICAL IMPEDANCE TOMOGRAPHY - Rymarczyk, Tomasz; Duda, Karol; Rymarczyk, Paweł; Olchowy, Daniel; Sikora, Jan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
This article presents the design of the device with active electrodes to examine the flood embankment. There was discussed the method of determining the conductivity. The presented solution was based on electrical impedance tomography. There was described the concept of active electrodes and measuring equipment for data acquisition. Electrical impedance tomography, which is based on measuring potential difference, can be used to calculate conductivity. The problem depends on the fact that every material has unique conductance.